The State and Healthcare - Rothgang, H. author. aut Link
XVIII, 278 p.
Keywords: Describes developments in healthcare systems over nearly four decades. Combining cross-sectional studies on healthcare financing, provision and policy values with in-depth country studies of Britain, Germany and the USA, this volume is a thorough examination of the convergence toward hybrid forms of healthcare systems.